TAT-HSP27 Peptide Improves Neurologic Deficits via Reducing Apoptosis After Experimental Subarachnoid Hemorrhage - Zhou, Xiao-yan; Sun, Jing-yi; Wang, Wei-qi; Li, Shu-xian; Li, Han-xia; Yang, Hui-juan; Yang, Ming-feng; Yuan, Hui; Zhang, Zong-yong; Sun, Bao-liang; Han, Jin-Xiang (Frontiers in Cellular Neuroscience, 2022)
Cell apoptosis plays an important role in early brain injury (EBI) after subarachnoid hemorrhage (SAH). Heat shock protein 27 (HSP27), a member of the small heat shock protein (HSP) family, is induced by various stress factors and exerts protective role on cells. However, the role of HSP27 in brain injury after SAH needs to be further clarified. Here, we reported that HSP27 level of cerebrospinal fluid (CSF) is increased obviously at day 1 in patients with aneurysmal SAH (aSAH) and related to the grades of Hunt and Hess (HH), World Federation of Neurological Surgeons (WFNS), and Fisher score. In rat SAH model, HSP27 of CSF is first increased and then obviously declined; overexpression of HSP27, not knockdown of HSP27, attenuates SAH-induced neurological deficit and cell apoptosis in the basal cortex; and overexpression of HSP27 effectively suppresses SAH-elevated activation of mitogen-activated protein Kinase Kinase 4 (MKK4), the c-Jun N-terminal kinase (JNK), c-Jun, and caspase-3. In an in vitro hemolysate-damaged cortical neuron model, HSP2765−90 peptide effectively inhibits hemolysate-induced neuron death. Furthermore, TAT-HSP2765−90 peptide, a fusion peptide consisting of trans-activating regulatory protein (TAT) of HIV and HSP2765−90 peptide, effectively attenuates SAH-induced neurological deficit and cell apoptosis in the basal cortex of rats. Altogether, our results suggest that TAT-HSP27 peptide improves neurologic deficits via reducing apoptosis.